Consent Capacity of Persons with Disabilities in Sexual Relations: A Comparative Legal Study of Indonesia, Canada, and the United Kingdom: Kapasitas Persetujuan Bagi Penyandang Disabilitas dalam Hubungan Seksual: Studi Perbandingan Hukum Indonesia, Kanada, dan Inggris - Azzahra, Sayyidina; Hutabarat, Rugun Romaida (Rechtsidee, 2025)
Background (General): Consent serves as the central boundary distinguishing lawful sexual relations from criminal sexual violence. Background (Specific): For persons with disabilities, assessing consent becomes more complex due to cognitive, mental, physical, or sensory limitations that may affect their ability to understand and communicate agreement. Knowledge Gap: Indonesian criminal law, including the UU TPKS, lacks explicit definitions of consent and standardized indicators for determining consent capacity, unlike jurisdictions such as the United Kingdom and Canada. Aim: This study examines Indonesia’s legal framework on sexual consent and evaluates the absence of consent-capacity standards for persons with disabilities through comparative analysis with UK and Canadian regulations. Results: Findings show that Indonesian law narrowly associates non-consent with coercion or threats, failing to consider cognitive incapacity, whereas the UK (Sexual Offences Act 2003; Mental Capacity Act 2005) and Canada (Criminal Code Section 153.1) provide clear criteria for assessing mental ability, voluntariness, and relational power imbalance. Novelty: This research identifies the structural legal gap in Indonesian consent-capacity regulation and proposes a model grounded in comparative jurisprudence. Implications: The study underscores the urgent need for legal reform to establish explicit consent-capacity standards, strengthening protection against sexual exploitation of persons with disabilities. Highlights: Highlights the absence of explicit consent-capacity standards in Indonesian law. Shows how UK and Canada provide clearer protections through defined legal criteria. Emphasizes the urgency of legal reform to safeguard persons with disabilities from exploitation. Keywords: Consent Capacity, Sexual Consent, Persons With Disabilities, Comparative Law, Indonesian Criminal Law